NILAI-NILAI RELIGIUS DALAM NOVEL UNTUKMU IMAMKU KARYA NUR HOIRIAH - Wa Ode Amalian Putri; Marwati; La Ode Balawa; Rachman (PT. CASA CENDEKIA MEDIA, 2025)
This research aims to describe and analyze religious values ​​in the novel Untukmu Imamku by Nur Hoiriah. The method used is descriptive qualitative with the type of library research. The data collected in this research is written data related to the religious values ​​contained in the novel. The data source comes from the novel Untukmu Imamku by Nur Hoiriah, published by Maple Books in 2022, with 296 pages. Data collection techniques use analytical reading techniques. Data were analyzed using a religious approach. Based on the research results, it can be concluded that the religious values ​​identified include several moral aspects, namely: (1) the value of patience , (2) the value of humility, (3) the value of trust, (4) the value of honesty, (5) the value of sincerity, and (6) the value of discipline.